A comparison of soil sampling procedures used to monitor soil fertility in permanent pastures - Friesen, DK; Blair, GJ (CSIRO Publishing, 1984)
Soil testing programs are often brought in disrepute by unexplained variability in the data. The deposition of dung and urine onto grazed pasture brings about marked variation in the chemical status of soils which contributes to this variability. A study was undertaken to compare a range of sampling procedures to estimate Colwell-P, Bray-1 P, bicarbonate K and pH levels in adjacent low and high P status paddocks. The sampling strategies used consisted of 75 by 50 m grids; whole and stratified paddock zig-zag and cluster (monitor plot) samplings. Soil test means for the various parameters did not vary among sampling methods. The number of grid samples required to estimate within 10% of the mean varied from 121 for Bray-1 P down to 1 for soil pH. Sampling efficiencies were higher for cluster sampling than for whole paddock zig-zag path sampling. Stratification generally did not improve sampling efficiency in these paddocks. Soil test means declined as sampling depth increased, but the coefficient of variation remained constant for Colwell-P and pH. The results indicate that cluster sampling (monitor plots) is the most appropriate procedure for estimating the nutrient status of grazed pastures. This sampling method enables a more accurate measure to be taken of the nutrient status of a paddock and should allow more reasonable estimates to be made of the temporal variations in soil test.